Melanie: A Novel Exploring How Trauma Affects a Teenager’s Mental Health - Jessie Tricia Evelyn Sherrie Adelina; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2023)
When a teenager accidentally commits a killing in self-defense, such an experience will have a tremendous effect on her psychological condition. From the accidental killing, she suffers from a post-traumatic stress disorder, which negatively affects her mental health. She will then use a variety of defense mechanisms to cope. This work applies the theory of traumatic stress, post-traumatic stress disorder, and defense mechanisms. This creative thesis is written in the form of a novel to showcase the effects of a self-defense killing on a person’s psyche, and how she uses defense mechanisms to deal with the effects. The novel shows how Melanie, the main character, suffers from the symptoms of post-traumatic stress disorder, such as strong emotions, overreaction, disturbed sleeping patterns, withdrawal from family and friends, depression, pessimistic outlook on life, and feelings of hopelessness, and she utilizes avoidance, acting out, repression and denial as defense mechanisms to deal with the stress.